Innovative Concept for Direct Customer Profiling as An Alternative or Complement to the Services of Global Players: The Example of Google, Meta, Tiktok - Grzegorz KRZOS; Jakub KOWALSKI (Communications of International Proceedings, 2025)
The purpose of this article is to present an innovative model for direct customer profiling AAET (Ask, Answer, Earn, Transform), based on the principle of direct and transparent exchange of value, i.e. marketing information for micropayments. In contrast to the currently dominant indirect model, associated with platforms such as Google or Meta, the AAET concept assumes full customer control over the process of transferring marketing data to the companies concerned and the elimination of external intermediaries. The article discusses the limitations of current models, points out the compatibility of the proposed solution with EU regulations (Data Governance Act, AI Act), and presents the impact of applying the AAET model on the efficiency of marketing, sales, production and logistics activities. Based on participant observation in two companies, the potential benefits of implementing the AAET model, such as increased conversions, improved data quality and increased customer loyalty, are demonstrated. The article concludes with a discussion of directions for further research and practical implications for the development of ethical and sustainable data management models.